2016
DOI: 10.1097/tp.0000000000000980
|View full text |Cite
|
Sign up to set email alerts
|

Early Measurement of Indocyanine Green Clearance Accurately Predicts Short-Term Outcomes After Liver Transplantation

Abstract: A simple score obtained within the first day after LT predicts short-term survival and need for retransplantation and may prove useful when selecting diagnostic and therapeutic strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 31 publications
0
28
0
7
Order By: Relevance
“…In spite of the initial enthusiasms and some very recent results, the use of post OLT ICG kinetics to predict morbidity and mortality are to be considered, at least in our opinion, still under scrutiny. Notwithstanding the results proposed by the most recent publication [59] , mixed results or "false pathological findings" (false positives) are present in the literature: To be specifically addressed in the liver transplant setting is the presence of hyperbilirubinemia. In this context, according to ICGPDR, newly grafted liver might be falsely classified as severely dysfunctioning or at consistent risk of unfavourable outcome, when opposite is the real final outcome.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…In spite of the initial enthusiasms and some very recent results, the use of post OLT ICG kinetics to predict morbidity and mortality are to be considered, at least in our opinion, still under scrutiny. Notwithstanding the results proposed by the most recent publication [59] , mixed results or "false pathological findings" (false positives) are present in the literature: To be specifically addressed in the liver transplant setting is the presence of hyperbilirubinemia. In this context, according to ICGPDR, newly grafted liver might be falsely classified as severely dysfunctioning or at consistent risk of unfavourable outcome, when opposite is the real final outcome.…”
Section: Resultsmentioning
confidence: 96%
“…In this context, according to ICGPDR, newly grafted liver might be falsely classified as severely dysfunctioning or at consistent risk of unfavourable outcome, when opposite is the real final outcome. In spite of the most recent evidence [59] , no consensus exists on the cut-off value of PDR/R15 below which a reliable assessment of early graft dysfunction is confidently available. In liver transplanted patients, the negative predictive value of ICG kinetics is indeed relevant: Good graft and patients outcome are almost always associated with "normal" IGC clearance parameters.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite only two of the reviewed articles included repeated measurements in the modelling process, repeated measurements of at least one of the candidate predictors were actually reported to be available in 6 (18.2%) of the articles [24,27,30,31,37,45]. Of these 6 articles that repeated measures were available, 4 of these had repeated measures that we categorised as being high risk [27,30,31,45], one of which used the repeated measures within the modelling [27].…”
Section: >> Insert Table 2: Predictors In Final Models At High Risk Omentioning
confidence: 99%
“…Acceptable accuracy of the PDD system has been reported after comparing data derived from invasive and non-invasive methods [23][24][25][26][27]. These non-invasive PDD systems have made the ICG clearance test more attractive even in Western countries, and many investigators have recently reported its usefulness as a non-invasive dynamic liver function test [28][29][30][31].…”
Section: Icg Clearance Testmentioning
confidence: 99%